MENYIMAK PUISI: ALTERNATIF DALAM MENGEMBANGKAN APRESIASI SASTRA DAN KARAKTER ISLAMI SISWA - Rahmani, Sabrina Putri; Aulia, Nisaul Firda; Mufida, Najwa Nuha; Mutari, Najwa Arni (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2026)
This study aims to explain listening to poetry as an alternative approach to developing literary appreciation and fostering students’ Islamic character. Through poetry listening activities, students are not only guided to understand aesthetic and linguistic aspects but also to internalize the moral and spiritual values contained within the poems. The research method employed is a qualitative approach with a library research design. Data were collected through document study and content analysis of relevant literature, while the data analysis technique followed the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that listening to poetry effectively enhances students’ literary appreciation by developing cognitive, affective, and aesthetic aspects in an integrated manner. Furthermore, this activity significantly contributes to shaping Islamic character traits such as honesty, patience, empathy, and gratitude through the internalization of moral values implied in poetic works. The implications of this study emphasize the importance of integrating poetry listening activities with Islamic educational values in the Indonesian language and literature curriculum, ensuring that learning is not only academically oriented but also focused on strengthening students’ character and spirituality in a holistic manner.